(untitled) (London Journal of Research In Science: Natural and Formal, 2025)
Microalgae are resources with several scientific and industrial uses, under this framework, the study aims to explore the possibility of taking advantage of the microalgae present in saline lagoons in southern Bolivia to obtain microalgae rich in ?-carotene. The microalgae samples were cultured in Erlemeyer flasks with Ben-Amostz Avron culture medium, by successive tests the Dunaliella salina was separated, later this inoculum was cultured in a 5-liter photobioreactor, then in 90 liters until reaching 140 liters culture using macronutrients and artificial light 20000 lux, it was possible to obtain microalgae composed of the Dunaliella salina known as the green phase, whose average cell density is 113929 cell/ml. From this phase, carotenogenic induction of the microalgae was carried out with the removal of nitrogen and phosphorus in the culture medium, the average content of ?- carotene in the red phase biomass was 12 mg/Li equivalent to 890 mg/100 g, and the conversion was 4.8 g ?-carotene/g chlorophyll, which contrasts with the fact that biomass contains a higher percentage ?-carotene. In the same way, it was possible to obtain biomass in the red phase by carotenogenic induction using natural light with 100000 lux maximum daily, the ?-carotene content was 4.26 mg/Li. This shows the feasibility of obtaining biomass rich in ?-carotene with natural light and macronutrients.